Thioredoxin‐interacting protein induced α‐synuclein accumulation via inhibition of autophagic flux: Implications for Parkinson's disease. (29th July 2017) - Su, Cun‐Jin; Feng, Yu; Liu, Teng‐Teng; Liu, Xu; Bao, Jun‐Jie; Shi, Ai‐Ming; Hu, Duan‐Min; Liu, Tong; Yu, Yun‐Li
Summary: Aims: Thioredoxin‐interacting protein (TXNIP) is associated with activation of oxidative stress through inhibition of thioredoxin (Trx). However, some evidences point out that TXNIP acts as a scaffolding protein in signaling complex independent of cellular redox regulation. The autophagy‐lysosomal pathway plays important roles in the clearance of misfolded proteins and dysfunctional organelles. Lysosomal dysfunction has been involved in several neurodegenerative disorders including Parkinson's disease (PD). Although researchers have reported that TXNIP inhibited autophagic flux, the specific mechanism is rarely studied. Methods: In this study, we investigated the effects of TXNIP on autophagic flux and α‐synuclein accumulation by Western blot in HEK293 cells transfected with TXNIP plasmid. Further, we explored the influence of TXNIP on DA neuron survival in substantia nigra by IHC. Results: We found that TXNIP induced LC3‐II expression, but failed to degrade p62, a substrate of autophagy. Also, TXNIP aggravated α‐synuclein accumulation. We also found that TXNIP inhibited the expression of ATP13A2, a lysosomal membrane protein. Moreover, we found that overexpression of ATP13A2 attenuated the impairment of autophagic flux and α‐synuclein accumulation induced by TXNIP. Furthermore, overexpression of TXNIP in substantia nigra resulted in loss of DA neuron. Conclusion: Our data suggested that TXNIP blocked autophagic flux and induced α‐synuclein accumulation through inhibition of ATP13A2, indicating TXNIP was a disease‐causing protein in PD.